THE INSPIRATION FROM "˜JINJU NAMGANG YUDEUNG FESTIVAL' FOR THE APPLICATION OF FABRIC MANIPULATION: THE TECHNIQUE OF SASHIKO - Khorimah, Fadila Vivi; Prayogo, Dina Natalia; Zahro, Siti; Juniati, Ninik (Home Economics Journal, 2024)
modern culture and the pleasant change in South Korea, with lanterns (yudeung) becoming the cultural icon for the festival. A visual analysis of this iconic lantern later produced a brilliant idea for fabric manipulation in the form of sashiko. The purpose of the research is to describe the process of stilation resulting from the visual analysis which was inspired by Jinju Namgang Yudeung Festival, a well-established tradition of the local community. This is process-based research focusing on the application of the stilation technique to fabric materials. The research found that the process of stilation resulting from the visual analysis of the lanterns using natural colors resulted in color palettes. The color was added to the thread used in the experiments. The visual analysis also resulted in stilation in the form of a geometric shape applied to fabric materials using a textile manipulation called the technique of sashiko. Sashiko is a technique of hand sewing adopted to embellish a fashion product. The garment manufactured using the technique of sashiko inspired by Jinju Namgang Yudeung Festival can be developed into ready-made products in the form of citywears.